Sistem Pakar Diagnosis Penyakit Kulit Balita Menggunakan Metode Certainty Factor dan Forward Chaining - Guon Fernando Tarimakase; Aris Gunaryati; Sari Ningsih (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
When someone has very weak immunity level, they can develop skin problems. Children, especially babies and toddlers, are prone to skin problems because their immune systems are not fully developed. Developing an application that can help users to be able to diagnose skin diseases in toddlers, especially skin diseases Diaper Rash, Prickly Heat, Chicken Pox, Measles, Eczema, and Impetigo is needed according to needs. This study uses the Forward Chaining inference engine and the Certainty Factor certainty method. The goal is to make an application that can help the experts to get information and solutions about skin diseases in toddlers, as well as to provide accurate presentations about the disease. In the development of this system, the resulted level of accuracy is in accordance with the diagnosis expert, which is equal to 83.33% of 30 medical record data